Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Interaktif Lectora Inspire Bagi Guru SD - Ana, Ria Fajrin Rizqy; Astutik, Leny Suryaning; Putri, Dya Ayu Agustina; Rachmadyanti, Putri; Rifayanti, Zuni Eka Tiyas (Universitas Pahlawan Tuanku Tambusai, 2026)
Advances in science and technology require teachers to creatively use interactive learning media. In reality, teachers rarely use interactive learning media during classroom instruction, resulting in low student motivation. To address this issue, a training program on creating technology-based learning media using Lectora Inspire was conducted. The objective of this training is to enhance teachers’ competencies in creating, developing, and implementing technology-based learning media. This training program consists of the following stages: 1) field survey (partners); 2) Coordination with school principals and teachers; 3) Program Socialization; 4) Program Implementation; and 5) Activity Evaluation. The results of the activities showed an increase in teachers’ knowledge and skills in designing innovative learning media. Additionally, teachers were able to produce learning media products that can be used in the classroom learning process. This program is expected to support more interactive learning, increase student motivation, and encourage the use of technology in elementary school education.